3D laminar natural convection in a cubical enclosure with gradually changing partitions. (April 2022) - Ugurlubilek, Nihal; Sert, Zerrin; Selimefendigil, Fatih; Öztop, Hakan F.
Abstract: In this paper, laminar natural convection heat transfer was numerically investigated in cubical air-filled enclosures with partitions attached to the walls with different positions. Steady-state governing equations were solved using the Boussinesq approximation by the finite volume method. Two cases were considered that the partitions were placed perpendicular (Case 1) and parallel (Case 2) to the active walls, respectively. The opposing lateral walls of the enclosure are heated and cooled while the other walls are adiabatic. The effect of the two inclined partitions attached to the bottom and top adiabatic walls at the different positions on the heat transfer rate was examined. The dimensionless partition heights and positions were h/H = 0.1, 0.2 and 0.3, and c/H = 0.25, 0.5 and 0.75, respectively. The inclination of the partitions was θ =3 °, 4 °, and 5 ° . The air ( Pr = 0.7) streamlines and the temperature fields were obtained for the Rayleigh numbers 10 3 ≤ Ra ≤ 10 6 for both cases studied. The mean dimensionless heat transfer ratio (Nusselt number) over the cold wall for both cases was also obtained. The effects of the dimensionless parameters considered on the heat transfer for both cases were concluded. It was seen that the parameters considered are important for Case 2 whereas they did not play a major role for Case 1. Highlights: The effect of dual partitions on the laminar natural convection in a cubical enclosure was investigated. The parameters are the dimensionless heights, positions and inclinations of the partitions. Novel correlations are derived for the cubical enclosure with dual partitions.